Chemical Modulators of Fibrinogen Production and Their Impact on Venous Thrombosis - Vilar, Rui; Lukowski, Samuel W.; Garieri, Marco; Di Sanza, Corinne; Neerman-Arbez, Marguerite; Fish, Richard J. (Thrombosis and Haemostasis, 2020)
Thrombosis is a leading cause of morbidity and mortality. Fibrinogen, the soluble substrate for fibrin-based clotting, has a central role in haemostasis and thrombosis and its plasma concentration correlates with cardiovascular disease event risk and a prothrombotic state in experimental models. We aimed to identify chemical entities capable of changing fibrinogen production and test their impact on experimental thrombosis. A total of 1,280 bioactive compounds were screened for their ability to alter fibrinogen production by hepatocyte-derived cancer cells and a selected panel was tested in zebrafish larvae. Anthralin and all-trans retinoic acid (RA) were identified as fibrinogen-lowering and fibrinogen-increasing moieties, respectively. In zebrafish larvae, anthralin prolonged laser-induced venous- occlusion times and reduced thrombocyte accumulation at injury sites. RA had opposite effects. Treatment with RA, a nuclear receptor ligand, increased fibrinogen mRNA levels. Using an antisense morpholino oligonucleotide to deplete zebrafish fibrinogen, we correlated a shortening of laser-induced venous thrombosis times with RA treatment and fibrinogen protein levels. Anthralin had little effect on fibrinogen mRNA in zebrafish larvae, despite leading to lower detectable fibrinogen. Therefore, we made a proteomic scan of anthralin-treated cells and larvae. A reduced representation of proteins linked to the canonical secretory pathway was detected, suggesting that anthralin affects protein secretion. In summary, we found that chemical modulation of fibrinogen levels correlates with measured effects on experimental venous thrombosis and could be investigated as a therapeutic avenue for thrombosis prevention.
Keywords: all-trans retinoic acid; anthralin; fibrinogen; thrombosis; zebrafish